Reestablishment of Amazonian species Eugenia pisonis (Myrtaceae) - Giaretta, Augusto; Carienne De Morais, Layra (Phytotaxa, 2023)
Eugenia pisonis is an Amazonian species here reestablished as distinguished from Eugenia moschata by leaf blades with conspicuous black dots ca. 1 mm from each other abaxially, apex abruptly long-acuminate, hypanthium glabrous or glabrate, sepals glabrous, petal globe in the bud markedly 4-costate, and fruit obovoid or oblate. Diagnostic characters are provided and imaged.